Aquaculture production systems (Wiley-Blackwell, 2012)
The systems examined range from low input methods to super-intensive systems. Divided into five sections that each focus on a distinct family of systems, Aquaculture Production Systems serves as an excellent text to those just being introduced to aquaculture as well as being a valuable reference to well-established professionals seeking information on production methods.